2013
DOI: 10.3989/scimar.03861.07b
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the abundance and spatial distribution of the Atlantic chub mackerel (<i>Scomber colias</i>) in the pelagic ecosystem and fisheries off Portugal

Abstract: SUMMARY: This study describes changes in abundance and spatial distribution of Atlantic chub mackerel in the Portuguese waters and the Spanish waters of the Gulf of Cadiz using data from acoustic surveys from 1995 to 2010 and data from the fishery since 1958. The distribution and dynamics of chub mackerel and sardine (Sardina pilchardus) are compared and species interactions are discussed. From 2007 to 2009, chub mackerel biomass, as measured acoustically, ranged between 69000 and 238000 t concentrated off the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 27 publications
1
25
0
1
Order By: Relevance
“…For chub mackerel only, there was a significant regional difference in its dietary importance, with higher numbers of this prey consumed in the southern area. This is consistent with higher estimated biomass and landings of chub mackerel in southern Portugal (Martins et al 2013, ICES 2016. This last observation gives some insight into the plasticity of common dolphin foraging behaviour, which not only demonstrates selection for favoured prey (sardine) and size-based selection, but also an element of opportunistic foraging, namely a diet composition which reflects regional abundance of prey.…”
Section: Dietary Preferences In Relation To Predator and Prey Size Ansupporting
confidence: 85%
See 1 more Smart Citation
“…For chub mackerel only, there was a significant regional difference in its dietary importance, with higher numbers of this prey consumed in the southern area. This is consistent with higher estimated biomass and landings of chub mackerel in southern Portugal (Martins et al 2013, ICES 2016. This last observation gives some insight into the plasticity of common dolphin foraging behaviour, which not only demonstrates selection for favoured prey (sardine) and size-based selection, but also an element of opportunistic foraging, namely a diet composition which reflects regional abundance of prey.…”
Section: Dietary Preferences In Relation To Predator and Prey Size Ansupporting
confidence: 85%
“…In order to remain economically viable, the fishing sector has since been forced to target other pelagic species, namely Atlantic chub mackerel, Scomber colias, and horse mackerel, Trachurus trachurus. Both species have recently shown increased biomass off the Portugal-Cadiz region and, for chub mackerel, especially an inverse relationship with abundance of sardine has been found (Martins et al 2013, ICES 2016.…”
Section: Introductionmentioning
confidence: 99%
“…The catches of small pelagic fish in the period under review (2007–2017) presented distinct trends: sardine and Atlantic horse mackerel showed a decreasing trend in catches while Atlantic chub mackerel showed an increasing pattern. The apparent switch from sardine to Atlantic chub mackerel catches could be related with an inverse correlation between the recruitment indices of the two species (Martins, Skagen, Marques, Zwolinski, & Silva, 2013), which could result from competition for food, predation or different response of each species to the same environmental conditions, because the fact that different species have different tolerance to abiotic factors (temperature, salinity).…”
Section: Discussionmentioning
confidence: 99%
“…• Existem algumas indicações de alterações para espécies não alvo, com os pelágicos a aumentar e a faneca a diminuir, que são corroboradas pelos dados de desembarques nos últimos anos (no caso dos pelágicos mesmo para embarcações locais fora do PMLS) e, no caso da cavala por literatura recente (e.g. Martins et al, 2013);…”
Section: Conclusõesunclassified